Clerkship director confidence in medical student career advising in obstetrics and gynecologyAJOG Global Reports at a Glance - Shireen Madani Sims, MD; Susan M. Cox, MD; Rashmi Bhargava, MD; Elise N. Everett, MD; Angela Fleming, DO; Scott Graziano, MD, MS; Helen K. Morgan, MD; Laura Baecher-Lind, MD, MPH; Celeste Royce, MD; Tammy S. Sonn, MD; Jill M. Sutton, MD; Christopher M. Morosky, MD, MS (AJOG Global Reports, 2023)
BACKGROUND: Given the increasing complexities of the residency application processes, there is an ever-increasing need for faculty to serve in the role of fourth-year medical student career advisors. OBJECTIVE: This study aimed to investigate obstetrics and gynecology clerkship directors’ confidence and fulfillment with serving in the role of faculty career advisors. STUDY DESIGN: A 25-item electronic survey was developed and distributed to the 225 US obstetrics and gynecology clerkship directors in university-based and community-based medical schools with active memberships in the Association of Professors of Gynecology and Obstetrics. Items queried respondents on demographics, confidence in fourth-year advising, satisfaction with this aspect of their career, and resources used for advising. RESULTS: Of 225 clerkship directors, 143 (63.6%) responded to the survey. Nearly all clerkship directors (136/143 [95%]) reported advising fourth-year students. A median of 5.0 hours (interquartile range, 3.0–10.0) was spent per student in this advisory role, with 29 of 141 clerkship directors (20.5%) reporting some form of compensation for advising. Confidence in the ability to advise fourth-year medical students correlated significantly with number of years as a faculty, number of years as a clerkship director, and a higher full-time equivalent allotted as clerkship director. Fulfillment as a faculty career advisor was correlated with number of years as a clerkship director and a higher number of students advised. CONCLUSION: Obstetrics and gynecology clerkship directors regularly serve in the crucial role of faculty career advisor. Confidence in advising fourth-year students, advising fulfillment, and satisfaction with advising resources were all significantly correlated. We recommend that clerkship directors review resources available for advising and that they be provided academic time to serve as career advisors.